Integrative Medicine for Postoperative Patients: A Survey of Korean Medicine Doctors. (31st July 2017) - Moon, Sun-Young; Shin, Kyung-Min; Shin, Jae-Young; Kwon, O-Jin; Lee, Jun-Hwan
Abstract : The purpose of this survey was to document the experience of Korean Medicine doctors (KMD) who provided postoperative care to patients through integrative medicine and to understand their opinions about integrative medicine utilization. Three researchers (two with a KMD license) of the Korea Institute of Oriental Medicine conducted the survey. The questionnaire was distributed via e-mail to the 17, 041 members of the Association of Korean Medicine in 2015. In total, 487 KMD answered the questionnaires. The majority of respondents worked in a Korean Medicine (KM) clinic, KM hospital, or long-term care hospitals (94.7%). The respondents mostly treated patients after musculoskeletal (26.7%), spinal (23.7%), or neuropathic surgery (22.2%). Patients predominantly experienced pain (23.0%), fatigue and tiredness (17.4%), delayed scar recovery (13.7%), and paralysis (13.0%). We analyzed subgroups in accordance with institution of employment, specialization, and clinical experience. Most KMD wanted to utilize integrative medicine for postoperative care of patients (92.6%). Moreover, a relatively active collaboration was noted in long-term care hospitals (mean rate: 60.73% [95% CI: 42.25 to 79.20]). Further studies and clinical trials are needed to determine whether integrative medicine is essential for providing postoperative care to Korean patients.